Bacteria, bile and the small bowel. Issue 12 (December 1969) - Gorbach, Sherwood L.; Tabaqchali, Soad
Abstract : Microbial populations of the small bowel and bile salt metabolism were studied in 15 patients with lesions of the stomach and small intestine. These types of microorganism could be correlated with the site and extent of stasis in the small bowel and the presence of a normally functioning stomach. The presence of obligate anaerobes (bacteroides) and free bile acids could be correlated with areas of stagnation. When these abnormalities were detected throughout the small bowel, steatorrhoea was also noted. However, bacteroides and free bile acids in localized regions of either proximal or distal small bowel were generally associated with normal faecal fat excretion. Vitamin B12 malabsorption appeared to be related to the total number of bacteria colonizing the small bowel rather than to any specific type of microorganisms. The effect of antibiotics on intestinal function and bacteriology was studied in three patients. In one patient, the broad-spectrum antibiotic tetracycline was effective in eradicating an abnormal bacterial flora. In the other two, lincomycin, which is specifically effective in eradicating the anaerobic flora, restored intestinal function to normal.